PENGEMBANGAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN KEKAYAAN BUDAYA INDONESIA SISWA KELAS IV SEKOLAH DASAR NEGERI 17 PONTIANAK KOTA - Pradikta, Diki; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Pradikta, D. 2024. Development of audio-visual media in learning Indonesian cultural wealth for grade IV Elementary School. Thesis, Elementary School Teacher Education Study Program, Elementary Education Department, Faculty of Teacher Training and Education, Tanjungpura University. This study aims to develop audio-visual media in the form of learning videos to support learning of Natural and Social Sciences (IPAS) on Indonesian Cultural Wealth for grade IV students of SDN 17 Pontianak City. The method used is research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study showed that the validity of the learning video product in the design aspect obtained a value of 4.39 with the criteria "Very Valid" and in the material aspect obtained a value of 4.40 with the criteria "Very Valid". This learning video media was designed using Microsoft PowerPoint, equipped with visual elements, animation, narration sound, and accompanying music that are relevant to student characteristics. Validation by design and material experts showed that this product is very valid for use.